Benefits and Risks of Antiretroviral Therapy for Perinatal HIV Prevention. Issue 3 (September 2017) - Fowler, M.G.; Qin, M.; Fiscus, S.A.; Currier, J.S.; Flynn, P.M.; Chipato, T.; McIntyre, J.; Gnanashanmugam, D.; Siberry, G.K.; Coletti, A.S.; Taha, T.E.; Klingman, K.L.; et al.
Abstract : ( N Engl J Med . 2016;375(18):1726–1737) Although triple-drug antiretroviral therapy (ART) has clear benefits for mothers and infants, studies have shown higher rates of adverse pregnancy outcomes with maternal ART than with regimens containing fewer antiretroviral agents. The Promoting Maternal and Infant Survival Everywhere (PROMISE) trial thus compared the relative efficacy and safety of various open-label antiretroviral strategies and their effect on preventing mother-to-child transmission among asymptomatic HIV-infected pregnant women with high CD4 counts (at least 350 cells/mm 3 ).